2007
DOI: 10.1083/jcb.200703187
|View full text |Cite
|
Sign up to set email alerts
|

Defective Ca2+ channel clustering in axon terminals disturbs excitability in motoneurons in spinal muscular atrophy

Abstract: Proximal spinal muscular atrophy (SMA) is a motoneuron disease for which there is currently no effective treatment. In animal models of SMA, spinal motoneurons exhibit reduced axon elongation and growth cone size. These defects correlate with reduced β-actin messenger RNA and protein levels in distal axons. We show that survival motoneuron gene (Smn)–deficient motoneurons exhibit severe defects in clustering Cav2.2 channels in axonal growth cones. These defects also correlate with a reduced frequency of local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
174
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(186 citation statements)
references
References 48 publications
(70 reference statements)
9
174
0
2
Order By: Relevance
“…PKA increases SMN complex formation and SMN stability. It has been reported that stimulation of cAMP results in increased FL-SMN levels (13,28). SMN contains three putative PKA phosphorylation sites identified by NetPhos 2.0 server (http: //www.cbs.dtu.dk/services/NetPhos) located at threonine 25, threonine 122, and serine 290 (3).…”
Section: Resultsmentioning
confidence: 99%
“…PKA increases SMN complex formation and SMN stability. It has been reported that stimulation of cAMP results in increased FL-SMN levels (13,28). SMN contains three putative PKA phosphorylation sites identified by NetPhos 2.0 server (http: //www.cbs.dtu.dk/services/NetPhos) located at threonine 25, threonine 122, and serine 290 (3).…”
Section: Resultsmentioning
confidence: 99%
“…5B,C), which showed colocalization of GFP-actin with phalloidin. We performed live cell imaging with mouse motoneurons at 5 days in culture because at this stage axon extension appears with highest speed and dynamics 28 (Fig. 4A, Suppl.…”
Section: Actin Dynamics Is Disturbed In C9orf72 Depleted or Mutated Mmentioning
confidence: 99%
“…However, how suboptimal levels of SMN lead to SMA is largely unknown. Multiple studies in SMA mouse models revealed widespread synaptic defects in neuromuscular junctions (NMJs), including neurofilament accumulation, poor terminal arborization, immature endplates, reduced quantal content, disturbed calcium homeostasis, and decreased remodeling potential; these defects precede motor neuron death (Cifuentes-Diaz et al 2002;Le et al 2005;Jablonka et al 2007;Kariya et al 2008;Murray et al 2008Murray et al , 2012Kong et al 2009;Ling et al 2010;Ruiz et al 2010;Lee et al 2011), suggesting that the NMJ alterations are the initial consequence of SMN deficiency, Ó 2015 Hua et al This article is distributed exclusively by Cold Spring Harbor Laboratory Press for the first six months after the full-issue publication date (see http://genesdev.cshlp.org/site/misc/terms.xhtml). After six months, it is available under a Creative Commons License (Attribution-NonCommercial 4.0 International), as described at http:// creativecommons.org/licenses/by-nc/4.0/.…”
mentioning
confidence: 99%